EFFECTIVENESS OF ELECTROLYZED OXIDIZING WATER FOR INACTIVATING Listeria monocytogenes IN LETTUCE - Casadiego Laíd, Paola; Laboratorio de Microbiología de Alimentos Departamento de Microbiología Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2005)
The effectiveness of electrolyzed oxidizing (EO) water for the inactivation of L. monocytogenes insuspension and when inoculated on lettuce leaves was evaluated. An electrolytic cell for the production of EO water was built and a solution of 5% NaCl was used. The EO water produced had a residual chlorine concentration of 29 parts per million (ppm) and pH 2.83. Ten strains of L. monocytogenes isolated from processed chicken (109 CFU/ml) were inoculated into 9 ml of EO water or 9 ml of deionized water (control) and incubated at 15°C for 5, 10, 15 and 20 min. The surviving population of each strain was determined on Columbia agar. An exposure time of 5 min reduced the populations by approximately 6.6log CFU/ml. The most resistant strains to sodium hypochlorite (NaOCl) were selected and used in a strain mixture (9.56 log CFU/ml, 109UFC/ml approximately) for the inoculation of 35 lettuce samples, by the dip inoculation method using distilled water as control. The population mean of L. monocytogenes after treatment with EO water and distilled water was reduced by 3.92 and 2.46 log CFU/ml respectively (p=0.00001). EO water and 6% acetic acid (vinegar) were combined to improve the EO water effect on L. monocytogenes inoculated in lettuce; the effectiveness of this combination was examined. The results showed that there was a synergistic effect of both antimicrobial agents (population reduction by 5.49 logCFU/ml approximately) on the viability of L. monocytogenes cells.